2020
DOI: 10.1007/s42832-020-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Mowing did not mitigate the negative effects of nitrogen deposition on soil nematode community in a temperate steppe

Abstract: Soil nematodes are the most numerous components of the soil fauna in terrestrial ecosystems. The occurrence and abundance of nematode trophic groups determine the structure and function of soil food webs. However, little is known about how nitrogen deposition and land-use practice (e.g. mowing) affect soil nematode communities. We investigated the main and interactive effects of nitrogen addition and mowing on soil nematode diversity and biomass carbon in nematode trophic groups in a temperate steppe in northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the meadow steppe, we also found that soil carbon stock was lower than the TG (Fig. S3), which may be due to that mowing reduced the accumulation of litter and then decreased the carbon input into soil (Chen et al 2019;Li et al 2020). The negative impacts of grassland degradation on aboveground biomass and non-significant effects on belowground biomass in this study resulted in an increase in root shoot ratio, which can change the plant biomass allocation (Gao et al 2008).…”
Section: Effects Of Grassland Degradation On Soil Qualitymentioning
confidence: 58%
“…In the meadow steppe, we also found that soil carbon stock was lower than the TG (Fig. S3), which may be due to that mowing reduced the accumulation of litter and then decreased the carbon input into soil (Chen et al 2019;Li et al 2020). The negative impacts of grassland degradation on aboveground biomass and non-significant effects on belowground biomass in this study resulted in an increase in root shoot ratio, which can change the plant biomass allocation (Gao et al 2008).…”
Section: Effects Of Grassland Degradation On Soil Qualitymentioning
confidence: 58%
“…Soil nematodes represent a major component of soil communities in terrestrial ecosystems, and play an important role in regulating nutrient cycling and soil health (Kouser et al, 2021;Li et al, 2021;Swanepoel et al, 2021;Wang et al, 2021). In the past few decades, the rapid development of molecular techniques has the potential to replace traditional morphological analysis (Floyd et al, 2002;Griffiths et al, 2018;Gao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%